PENGARUH PENDIDIKAN KESEHATAN TENTANG KANKER PAYUDARA DAN PERIKSA PAYUDARA SENDIRI TERHADAP PENGETAHUAN, PERSEPSI, DAN KETRAMPILAN IBU - Arlyana Hikmanti; Dina Febrina (Universitas Harapan Bangsa Purwokerto, 2018)
Breast cancer is a disease that attacks many women. About 60-70% of patients present at an advanced stage, III or IV, and more than 50% of the incidence of breast cancer ends in death. This number continues to increase, although breast cancer prevention screening can be done with breast mammography / ultrasound. Lack of knowledge about risk factors, and breast cancer associated with delays in patients with breast cancer have an impact on the wrong perception, delay in detection of breast cancer, 5 and delay in the diagnosis of breast cancer. The provision of health education can improve the patient's behavior in management through increased self-knowledge, perception, and breast self-examination practices. The purpose of this study was to determine the effect of health education on breast cancer and BSE on the knowledge, perceptions and skills of mothers in the Padamara Health Center area. This research is a Quasi Experimental Design research with One-Group Pretest-Posttest Design approach. The sampling technique uses quota sampling, a total of 30 mothers. Data analysis is in the form of univariable analysis, bivariable analysis using paired t test, data is normally distributed. The results showed that there was an effect of health education on the level of knowledge (p = 0.002), perception (p = 0.006), and maternal skills (p = 0.000). Keywords: health education, knowledge, perception, skills, breast cancer.